Switchability of Gabapentin Formulations: A Randomized Trial to Assess Bioequivalence Between Neurontin and Gabasandoz on the Individual Subject Level. Issue 1 (2nd March 2019) - Van Lancker, Griet; Van Bortel, Luc; Delafontaine, Brant; Boussery, Koen; Swart, Eleonora; Chahbouni, Abdel; Van Bocxlaer, Jan; Colin, Pieter
Abstract : Generic substitution of antiepileptic drugs is generally not advised by neurologists. The present study investigated the switchability of gabapentin 800 mg tablets (Neurontin and Gabasandoz) using an individual bioequivalence (IBE) study design with two batches of each product and assessed whether between‐batch and between‐formulation variability in exposure play a significant role in the within‐subject variability. The trial was analyzed according to the US Food and Drug Administration (FDA) framework to establish IBE. The IBE was shown between both products with the 95% upper confidence bound of the IBE criterion being −2.01 and −2.31 for area under the concentration‐time curve from zero to infinity (AUC0–inf ) and peak plasma concentration (Cmax ), respectively. Subject‐by‐formulation variability (1.35%) was negligible compared with the within‐subject variability of AUC0–inf with Neurontin (19.0%) and Gabasandoz (23.6%). Inclusion of an additional batch did not significantly change this within‐subject variability (20.2% and 23.6%, respectively). This study shows that substitution of gabapentin 800 mg tablets of Neurontin and Gabasandoz should be possible without affecting clinical outcomes.